Metabolic syndrome in relation to cognitive function and white matter integrity in midlife: The CARDIA study. (31st December 2021) - Dintica, Christina S; Allen, Norrina; Sidney, Stephen; Yaffe, Kristine
Abstract: Background: Metabolic syndrome (MetS) has been associated with poorer cognition in old age, however this association has yet to be defined in midlife. We aimed to investigate the relationship of early adulthood to midlife MetS in relation to cognition and white matter integrity in midlife. Methods: Within the prospective study of Coronary Artery Risk Development in Young Adults, 2882 participants were identified with follow‐up of 30 years (age 18–30 years at baseline). MetS was defined using National Cholesterol Education Program guidelines and assessed across 9 follow‐ups over 25 years. Cognitive function was assessed at Year 30 using the Rey Auditory Verbal Learning Test (verbal memory), Digit Symbol Substitution Test (processing speed), Stroop test (executive function) and Verbal Fluency. Using logistic regression, we examined the association of MetS at Year 25, and persistent MetS (at least two assessments over the follow‐up) with poor mid‐life cognition, defined as ≥1 standard deviation below the mean in each domain. In a sub‐sample (n=453), brain MRI measures of total and region‐specific white matter integrity (fractional anisotropy [FA] and mean diffusivity [MD]) were assessed at Year 30 (mean age of 55±3.5 years) and converted to standardized z‐scores. Results: MetS at Year 25 (n=534, 18.54%) was associated with poor cognitive function five years later in verbal memory (OR: 1.32, 95% CI: 1.04; 1.67) and processing speed (OR: 1.59, 95% CI: 1.23; 2.05), adjusting for age, sex, education, race, income, and smoking. Similarly, participants with persistent MetS over 25 years had lower cognitive performance in verbal memory (OR: 1.38, 95% CI: 1.10;1.73) and processing speed (OR: 1.72, 95% CI: 1.34; 2.22). In the MRI sub‐sample, MetS at Year 25 (n=60, 13.3%) was associated with lower total FA (β: ‐0.31, 95% CI: ‐0.57; ‐0.05). Persistent and non‐persistent MetS was associated with lower frontal FA (β: ‐0.36, 95% CI: ‐0.62; ‐0.09, β: ‐ 0.21, 95% CI: ‐0.62; ‐0.08, respectively) and higher total MD (β: 0.30, 95% CI: 0.03; 0.56, β: 0.26, 95% CI: 0.01; 0.51, respectively). Conclusion: MetS from early adulthood to midlife may be a risk factor for poor cognitive function in midlife and is associated with microstructural white matter differences.